(untitled) (Advances in Applied Mathematics and Mechanics, 2024)
In this work, the types of shock wave structure for hydro-elastoplastic model under compression are researched. The emphasis focuses on the theory of shock transition in the presence of elastic-plastic-fluid phase transition. As a result, in addition to the classical three-wave structure, two new shock wave patterns are found with the increase of loading strength. Several numerical tests are presented to verify the existence of the three types of wave structure.